TelAP2 links TelAP1 to the telomere complex in Trypanosoma brucei - Nadine Weisert; Verena Majewski; Laura Hartleb; Katarina Luko; Liudmyla Lototska; Nils Christian Krapoth; Helle D. Ulrich; Christian J. Janzen; Falk Butter (Scientific Reports)
Abstract The extracellular parasite Trypanosoma brucei evades the immune system of the mammalian host by periodically exchanging its variant surface glycoprotein (VSG) coat. Hereby, only one VSG gene is transcribed from one of 15 subtelomeric so-called bloodstream form expression sites (BES) at any given timepoint, while all other BESs are silenced. VSG gene expression is altered by homologous recombination using a large VSG gene repertoire or by a so-called in situ switch, which activates a previously silent BES. Transcriptional activation, VSG switching and VSG silencing during developmental differentiation from the bloodstream form to the procyclic form present in the tsetse fly vector are tightly regulated. Due to their subtelomeric position, telomere-associated proteins are involved in the regulation of VSG expression. Three functional homologs of mammalian telomere complex proteins have been characterized thus far, and novel telomere-interacting proteins, such as telomere-associated protein 1 (TelAP1), have recently been identified. Here, we used mass spectrometry-based proteomics and interactomics approaches, telomere pull-down assays with recombinant material and immunofluorescence analysis to elucidate the interactions of 21 other putative TelAPs. We investigated the influence on VSG expression and showed that depletion of TelAPs does not ultimately lead to changes in VSG expression. Additionally, we examined the interaction patterns of four TelAPs with the TbTRF/TbTIF2/TbRAP1 telomere complex by reciprocal affinity purification. We further propose that TelAP1 interacts with Tb927.6.4330, now called TelAP2, and that TelAP1 depends on this interaction to form a complex with the telomeric proteins TbTRF, TbTIF2 and TbRAP1.